Law, state and working class organisation in Uganda, 1962-1987 - Barya, John-Jean B. (1990)
This thesis describes and interprets the historical development of the legal regulation of the Ugandan trade union movement and assesses the relative importance of law in the determination of the character of trade union organisation in the post-colonial period 1962-1987. Chapter I defines the scope of the thesis and identifies the theoretical framework and analytical themes on which the thesis is based. Chapter II deals with the colonial foundations of the post-colonial legislation with which the thesis is mainly concerned. Chapters III, IV and V cover the period 1962-1987 whereby we analyse, first, the class and political character of the legal changes that take place between 1963-1976. Secondly, we examine the practical operation and impact of the law vis-a-vis the role of state policy and behaviour, the ideological outlook adopted by the trade unions, union constitutional structures and leadership struggles in the formation of the character of contemporary trade unionism in Uganda. The thesis treats law as a historical category and takes as its starting point the Marxist conceptualisations which view law variously as an instrument of the dominant class, as ideology or which attempt a materialist analysis. From these perspectives we examine the processes of class struggle through which the specific legislation came into being and more crucially the importance of the balance of class forces in the practical utilisation of legal rights or restrictions. We conclude in Chapter VI that while the economic parameters in which trade unions exist and operate are important determinants of union character, within those parameters the character of the state has proved to be most crucial. But at the level of the unions themselves, the ideology they adopt, their constitutional structures and leadership struggles, together, have created the contemporary undemocratic, economistic-apolitical and technocratic aspects of trade unionism in Uganda. However law has been important for the unions to the extent that it has been mainly a source of legitimation for their autonomous existence, most of the time, in their chequered history. The analysis of the historical and class origins and nature of the law regulating trade union organisation and the assessment we make of the role of law vis-a-vis the role played by other factors in determining the character of trade union organisation in Uganda is, in our view, an original contribution to the knowledge of industrial relations law in Uganda. The construction and interpretation of the historical phases through which both trade union law and trade union organisation have passed is likewise an original contribution to the knowledge of trade unionism in Uganda.